Advanced electrolyte tuning and selectivity enhancement for highly sensitive analysis of cations by capillary ITP–ESI MS. Issue 5 (5th February 2013) - Malá, Zdena; Pantůčková, Pavla; Gebauer, Petr; Boček, Petr; Gaš, Bohuslav
<x xml:space="preserve">Abstract</x> In this contribution we present an innovative way to easy, fast, and highly sensitive analyses by CE with ESI‐MS detection. The new method is designed to be applied to ESI‐compatible electrolytes (e.g. ammonium acetate) and offers advanced tuning of selectivity conditions within a wide range of analyte mobilities. We use a full capillary ITP format to provide powerful on‐line analyte stacking at the ITP boundary all the way to detection and introduce the model of extended ITP where a controlled concentration of the leading ion is added to the terminating zone. Such systems preserve all properties of an ITP system and the velocity of the stacking ITP boundary can be tuned by the composition of both the leading and terminating zone. In this way, the system properties can be controlled flexibly and the mobility window of stacked analytes can be tailored to actual needs. The presented theory and the newly defined concept of zone‐related boundary mobility allow easy assessment of system selectivity using simple diagrams. We demonstrate the model and its potential on the example of simple acidic cationic systems composed of only two substances (ammonium and acetate) including the example of thiabendazole analysis with a detection limit of 10−10 M (20 ng/L) and its determination in orange juice by direct sampling after filtration, selective stacking by a tuned extended ITP system, and ESI‐MS detection.